Implementation of Arabic Language Learning From an Integration Theory Perspective on Reading Ability - Muhammad Tareh Aziz; M. Abdul Hamid; Nurhadi Nurhadi (JETL (Journal of Education, Teaching and Learning), 2025)
Arabic language learning in Indonesia still needs to improve for Arabic language learners at the high school level, except for learning at Madrasah Aliyah Muallimin Muallimat Jombang, which is different from other schools. The advantage of this school is that its students can have the skills to read Arabic. This research shows that: 1) Implementation of the specific objective aspects of Arabic language learning material is interconnected and interrelated between one subject and another. The aim is for students to have read, 2) The implementation of Arabic language learning material is multidisciplinary, with the existence of linkages and mutual support between Arabic language learning material and religious material as well as a combination of classic Arabic and modern Arabic material. 3) The implementation of the method in this school is divided into two parts, namely the first method outside the classroom, which consists of prayer and reading aliyah together; the second method in learning is the integration of grammar and translation methods, singing methods, writing methods, reading methods, as well as audiolingual methods. 4) Two evaluations were used: the learning evaluation, which used daily, formative, and summative evaluations. Second, learning evaluation to determine the achievement of school goals by using two evaluation models in the final grade, namely a book reading test and a comprehensive test.